1991
DOI: 10.1016/0165-4608(91)90457-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical, cytogenetic, and molecular aspects of Ph-negative CML

Abstract: Between 1985 and 1989. many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…This distribution is consistent with the reported incidence of bcr/ abl positive disease among patients with Ph negative CML. 9,12,15,19,23,24,33,51 Our findings in a large and strictly defined study group confirmed the results of our previous report 23 and the results of other authors, 1,3,[5][6][7]52,53 namely, that patients with Ph negative CML have a poor prognosis. The median survival was 24 months, with only 7% of patients surviving beyond 5 years.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This distribution is consistent with the reported incidence of bcr/ abl positive disease among patients with Ph negative CML. 9,12,15,19,23,24,33,51 Our findings in a large and strictly defined study group confirmed the results of our previous report 23 and the results of other authors, 1,3,[5][6][7]52,53 namely, that patients with Ph negative CML have a poor prognosis. The median survival was 24 months, with only 7% of patients surviving beyond 5 years.…”
Section: Discussionsupporting
confidence: 81%
“…50,64 The causes of death among patients with bcr/abl negative CML are controversial. One study 26 suggested that increased tumor load and bone marrow failure is a more frequent cause of death compared with evolution into a blastic phase, which is very common in patients with bcr/abl positive CML, whereas another study 19 reported frequent transformation into the blastic phase. In our cohort of patients with bcr/abl negative CML, progression to the blastic phase was documented in 31% of patients for whom the cause of death was known.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of atypical CML display a high incidence of complex karyotypes involving both chromosome 5 or 7, similar to myelodysplastic syndromes and secondary acute myeloid leukemia. 1,24 In contrast to chronic myelogenous leukemia and a large proportion of the other subtypes of chronic myeloproliferative disorders, the molecular pathogenesis of CMML is still only minimally understood. Mutations of RAS are detected in approximately one-third of CMML cases.…”
Section: Cytogenetic Resultsmentioning
confidence: 99%
“…Thus, Ph chromosome or the bcr/abl fusion gene serves as the hallmark of CML and also as a prognostic marker during the treatment of CML with interferon or bone marrow transplantation (BMT). [2][3][4][5][6][7] Until recently, detection of Ph chromosome has been primarily done by karyotype analysis of freshly obtained bone marrow cells. The major limitation of the karyotypic technique is an absolute need for metaphases in testing cells.…”
Section: Introductionmentioning
confidence: 99%